ANALISIS OUTPUT BADAN USAHA MILIK DESA DALAM PENINGKATAN EKONOMI PENERIMA MANFAAT PROGRAM KELUARGA HARAPAN (STUDI PADA BADAN USAHA MILIK DESA KARYA MEKAR SUKAJADI CIANJUR) - Sonuari, Mochammad Ikbal; Nugroho, Fentiny (Istek Widuri Jakarta, 2019)
This study aims to analyze the output of BUMDes in increasing Beneficiary Families of Program Keluarga Harapan (PKH). This research was conducted at BUMDes Karya Mekar Sukajadi Village, Campaka District, Cianjur Regency. BUMDes Karya Mekar is one of the BUMDes that involves beneficiaries of the Program Keluarga Harapan (KPM PKH) in the BUMDes business venture. Beneficiaries of the Program Keluarga Harapan or KPM PKH are categorized into Poor Household category.This research was conducted using a qualitative approach and employing in-depth interview and observation techniques. This research study shows that through BUMDes, KPM is involved in order to provide them with an opportunity to run business for improving their economic conditions. It is a supporting element to assist the KPM to be economically self-reliant. The results of the study have shown that BUMDes provides output to the beneficiaries of the Program Keluarga Harapan. BUMDes provides the KPM with: 1) Access to business opportunities; 2) Increase in family income; 3) Easy access to capital goods; 4) Enhancing financial management knowledge; and 5) Accelerating the independent graduation of the Program Keluarga Harapan.